Zalacca Based Food Industry Development in Karang Asem District Bali Province - Made Yuliartini; Luh Kartini; Ida Bagus Komang Mahardika; A.A. Made Semariyani; I Gede Pasek Mangku; Yohanes Parlindungan Situmeang; I Komang Jiwa Antara; I Gusti Ngurah Agung Pawana; M. Pambudi Nurwantara; I Gusti Bagus Udayana; Ni Made Defy Janurianti; AA Mayun Wirajaya (SEAS (Sustainable Environment Agricultural Science), 2020)
The food industry is one of the industries that is growing very rapidly throughout the world, including in Indonesia. Various types of food and beverages with an attractive appearance continue to be produced to increase the aesthetic value and attractiveness of consumers. Food and beverage production processes include the selection of raw materials, food and beverage processing, food and beverage quality testing, packaging to the food and beverage distribution process. Every process that takes place must be controlled so that the final product produced is safe and suitable for consumption by consumers. Zalacca production in Karangasem Regency is very good to be developed into the useful food industry. The development of the zalacca-based food industry can increase added value for the people and zalacca commodities. The results of the study using the Process Hierarchy Analysis methodology show that Chips, Syrups, and Extracts occupy high yields to be developed.